The star formation history and the nature of the mass-metallicity relation of passive galaxies at 1.0 < z < 1.4 from VANDELS - Saracco, Paolo; Barbera, F La; De Propris, R; Bevacqua, D; Marchesini, D; De Lucia, G; Fontanot, F; Hirschmann, M; Nonino, M; Pasquali, Anna; Spiniello, C; Tortora, C (Monthly notices of the Royal Astronomical Society, 2023)
We derived stellar ages and metallicities [Z/H] for ∼70 passive early-type galaxies (ETGs) selected from VANDELS survey over the redshift range 1.0 < z < 1.4 and stellar mass range 10 < log(M*/M⊙) < 11.6. We find significant systematics in their estimates depending on models and wavelength ranges considered. Using the full-spectrum fitting technique, we find that both [Z/H] and age increase with mass as for local ETGs. Age and metallicity sensitive spectral indices independently confirm these trends. ...